Gestão de marketing e operações no serviço público: a qualidade como fator determinante de satisfação na utilização dos serviços prestados pela pró-reitoria de gestão de pessoas de uma instituição federal de ensino superior - Faria, Luciano Lamounier (2019)
Over the years the public sector has gained visibility, raising the level of demand for quality services, both internally and externally to organizations. It is in this scenario that the Human Resources Office at the Federal University of Uberlandia provides a wide range of services to its civil servants, in order to guarantee their access to rights and benefits, but also their awareness about the duties to be fulfilled according to the law. Despite criticisms regarding the use of managerial practices in the public service, evidenced in the last decades of the twentieth century by the New Public Management movement, the use of fluid management foundations was the objective of this study. This research aimed to identifying the satisfaction level of the civil servants of the University, Professors and Administrative Technicians in Education, on the quality of the services provided. In addition, considering topics of Marketing and Operations Management in the public sphere, this research also aimed to indicate aspects that deserve intervention of the management team to better meet the needs of its target audience. In order to do so, a bibliographic review was carried out on quality, institutional identity, institutional image, satisfaction and perceived value constructs, followed by the application of online questionnaires to civil servants in activity at the Institution's Santa Monica campus. Semistructured interviews were also conducted with the directors of the Human Resources Office, to obtain the necessary inputs to test hypotheses and identify the impressions about the existing services. Data were analyzed by descriptive statistics and content analysis. The results confirmed significant and positive effects among the constructs: quality has an effect on the institutional image, perceived value and satisfaction; perceived value and institutional image exert an effect on satisfaction. Professors and Administrative Technicians in Education awarded very close marks for quality. The accomplishment of this research brings academic and managerial contribution for investigating the provision of services in the university environment and providing material with critical consistency and indication of improvement points.